Domestic Violence and the Law: A Study of Complaints Under the Protection of Women From Domestic Violence Act, 2005 in Maharashtra, India - Panchal, Trupti Jhaveri (Violence against women, 2023)
Violence against women is a complex phenomenon that is deeply embedded in Indian society. In this mixed methods article, court records data (2005–2010) from two sites in Maharashtra, India along with in-depth interviews with stakeholders were analyzed to examine the implementation of the Protection of Women from Domestic Violence Act, 2005 (PWDVA). Out of 77.28% married women who filed a case under the PWDVA, 60.28% of them reported dowry-related harassment. Maharashtra has the social infrastructure in place to implement the law, although optimal use needs to be ensured for speedy delivery of justice.